Impact of Vanadium Complexes Treatment on the Oxidative Stress Factors in Wistar Rats Plasma - R. Francik; M. Krosniak; M. Barlik; A. Kudla; R. Grybos; T. Librowski (Bioinorganic Chemistry and Applications)
The aim of this study was to investigate the clinical efficacy of vanadium complexes on triglycerides (TG), total cholesterol (Chol), uric acid (UA), urea (U), and antioxidant parameters: nonenzymatic (FRAP—ferric reducing ability of plasma, and reduced glutathione—GSH) and enzymatic (glutathione peroxidase—GPx, catalase—CAT, and GPx/CAT ratio) activity in the plasma of healthy male Wistar rats. Three vanadium complexes: [VO(bpy)2]SO4⋅2H2O, [VO(4,4′Me2bpy)2]SO4⋅2H2O, and Na[VO(O2)2(bpy)]⋅8H2O are administered by gavage during 5 weeks in two different diets such as control (C) and high fatty (F) diets. Changes of biochemical and antioxidants parameters are measured in plasma. All three vanadium complexes statistically decrease the body mass growth in comparison to the control and fatty diet. In plasma GSH was statistically increased in all vanadium complexes-treated rats from control and fatty group in comparison to only control group. Calculated GPX/CAT ratio was the highest in the control group in comparison to others.